Design of a Compact UWB Antenna with Triple Band-Notched Characteristics - Qiang Wang; Yan Zhang (International Journal of Antennas and Propagation)
A new compact ultra-wideband (UWB) antenna with triband-notched characteristics is presented. The structure of the proposed antenna is simple and symmetric. A modified ground is introduced to obtain a wide impedance bandwidth of 2.9–13.4 GHz with S11<-10 dB. By inserting two arc-shaped slots in the radiation patch, two sharp bands of 3.3–3.7 GHz and 5.15–5.35 GHz are notched. The notch band of 7.25–7.75 GHz is achieved by etching a U-shaped slot in the ground plane. The notched bands can be controlled, respectively, while the characteristics of the proposed UWB antenna almost keep completely unchanged at the unnotched frequencies. Equivalent circuit models, surface current distributions, and input impedance are applied to analyze the principle of the proposed UWB antenna. Parametric studies are given. Simulated and measured results show that the proposed antenna has good impedance matching, stable radiation patterns, and constant gain.